2022
DOI: 10.3389/feart.2022.966558
|View full text |Cite
|
Sign up to set email alerts
|

Geological and geomorphological evidence of holocene activity along the maisu fault in the northern Sichuan–Yunnan block, Tibetan Plateau

Abstract: The Sichuan–Yunnan block is located in the eastern of Tibetan Plateau and exhibits strong tectonic and earthquake activity. The Maisu fault is an E–W-trending fault within this block. Via interpretations of remote-sensing imagery and field surveys, we identified a earthquake surface rupture zone that has developed along the Maisu fault; we then estimated its Holocene activity. The surface rupture extends westward from the town of Puma, Sichuan Province, to the village of Worilong, Xizang Province, and has a le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Relevant studies have shown that the slip rate of the Batang fault since the Late Quaternary has been 2.21-3.7 mm/a (Huang et al, 2015;Wang et al, 2015;You et al, 2016), and some studies have suggested that the Batang fault has decomposed the strike-slip deformation of the Garzê-Yushu fault, which has led to change in the slip rate of the Garzê-Yushu fault (Huang et al, 2015;Lv et al, 2017). In addition, related studies also believe that the Maisu fault likely accommodates the partitioned horizontal slip deformation of the Garzê-Yushu fault (Zuo et al, 2022). The Abuduo fault is a leftlateral strike-slip fault with Holocene activity, and its tendency is similar to that of the Batang fault and Maisu fault, i.e., both have near E-W alignment, and the eastward extension of the Abuduo fault is likely to intersect the Garzê-Yushu fault.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Relevant studies have shown that the slip rate of the Batang fault since the Late Quaternary has been 2.21-3.7 mm/a (Huang et al, 2015;Wang et al, 2015;You et al, 2016), and some studies have suggested that the Batang fault has decomposed the strike-slip deformation of the Garzê-Yushu fault, which has led to change in the slip rate of the Garzê-Yushu fault (Huang et al, 2015;Lv et al, 2017). In addition, related studies also believe that the Maisu fault likely accommodates the partitioned horizontal slip deformation of the Garzê-Yushu fault (Zuo et al, 2022). The Abuduo fault is a leftlateral strike-slip fault with Holocene activity, and its tendency is similar to that of the Batang fault and Maisu fault, i.e., both have near E-W alignment, and the eastward extension of the Abuduo fault is likely to intersect the Garzê-Yushu fault.…”
Section: Discussionmentioning
confidence: 95%
“…Among the three near E-W-trending faults within the study area, the Batang fault is a left-lateral strike-slip fault with Holocene activity that has had a horizontal slip rate of 2.1-3.9 mm/a since the Late Quaternary, and presents a paleoseismic recurrence cycle of approximately 1,500 years (Huang et al, 2015;You et al, 2016). The Maisu fault is on the southern side of the Garzê-Yushu fault, and geomorphological evidence suggests that it also has Holocene activity, with a predominant left-lateral characteristic (Zuo et al, 2022). Seismological-geomorphological evidence associated with the Abuduo fault also indicates that it is a left-lateral strike-slip fault with Holocene activity, and that it extends eastward to intersect the Garzê-Yushu fault near Zhengke.…”
Section: Tectonic Settingmentioning
confidence: 99%
See 1 more Smart Citation